A LONG HISTORY OF THE SALAKANAGARA KINGDOM - Beslina Siagian; Pontas Jamaluddin Sitorus; Romasdo Sigalingging; Glory Intania Br Sitanggang (Media Inovasi Pendidikan dan Publikasi, 2023)
The purpose of this study is to find out the long history of the Salakanagara kingdom. The method used in this study is a qualitative approach, and uses a descriptive research type, namely a formulation of the problem that guides the research to be able to explore, provide an overview and analyze the findings of the data in the field as a whole, broadly and intensively from the informants. This study explains and provides an overview of the long history of the kingdom of Salakanagara (Pandeglang, Banten). The Salakanagara Kingdom is only a Regional Kingdom. When led by Dewawarman VIII, the people of the Salakanagara kingdom prospered and lived happily. The decline of Salakanagara began in the 362nd century AD led by Dewawarman IX, not long after the birth and development of the Tarumanegara kingdom. The Salakanagara Kingdom was taken over to become a new part of the Tarumanegara kingdom.